Polish Employment Law in the Face of Digitization and New Technologies (Contemporary Central & East European Law, 2020)
The digital revolution, also called the fourth industrial revolution, constitutes another era of change, caused by the development of computerisation and modern technologies. It is characterised by rapid technological progress, widespread digitisation and an impact on all areas of life, including the provision of work. The changes affecting this area are so significant that there are proposals to remodel the definition of the employment relationship in the Labour Code. New forms of employment, which do not fit the conventional definition of an employment relationship, are emerging and gaining importance. An example could be employment via digital platforms. At the same time, there are also employment forms that do fit that definition, but deviate from the conventional understanding of the terms and conditions for performing work, which have undergone modification due to the use of new technologies. Teleworking, or working outside the employer’s premises, are examples of that. Employers get further opportunities to organise and control work, which often raises concerns due to the employee’s right to privacy, the protection of personal rights and personal data.